Left Atrial Myocardial Mechanics: Association With Cognitive Dysfunction, Cerebrovascular Disease, and Circulating Biomarkers - Tan, Eugene S. J.; Hilal, Saima; Chan, Siew Pang; Sim, Ming Ann; Lai, Mitchell K. P.; Chong, Joyce; Robert, Caroline; Hazli, Hazliza; Gong, Lingli; Berboso, Josephine Lunaria; Venketasubramanian, Narayanaswamy; Tan, Boon‐Yeow; et al. (Journal of the American Heart Association, 2025)
The relationship of left atrial (LA) strain with cognition in the absence of atrial fibrillation is poorly understood. We investigated the association of LA strain with cognitive impairment and its pathogenetic subtype (vascular [VCI] or neurodegenerative) and underlying mechanisms via associations with circulating and neuroimaging markers of cerebrovascular disease. LA strain (reservoir, conduit [LAScd], contractile) was determined using speckle-tracking echocardiography in a prospective memory clinic cohort with brain magnetic resonance imaging, neuropsychological assessments, and circulating biomarker measurements. Cognitive impairment was classified as VCI or neurodegenerative in the presence or absence of significant cerebrovascular disease, respectively. Among 251 subjects (age 75±8 years, 59% women) without atrial fibrillation, 178 (71%) had cognitive impairment (20% mild, 14% moderate, 37% dementia); of these impairments, 58% were VCI and 42% neurodegenerative. Only LAScd was associated with more severe cognitive impairment (moderate/dementia versus none/mild, adjusted odds ratio [aOR] for lowest versus highest tertile >2) and specifically, with worse Mini-Mental State Examination score and memory on neuropsychological testing. LAScd was independently associated with VCI (versus neurodegenerative; aOR for lowest versus highest tertile, 4.22 [95% CI, 1.59-11.2]) and not with neurodegenerative markers (circulating pTau-181 [phosphorylated tau-181], isolated lobar cerebral microbleeds). Both LAScd and LA reservoir strain were associated with increased burden of cerebral small vessel disease on magnetic resonance imaging, but only LAScd correlated with circulating biomarkers, reflecting inflammation, neurotrophic processes, and neuronal damage. Reduced LA strain was associated with cognitive impairment, primarily of vascular origin, and a higher burden of cerebral small vessel disease. LAScd may be a biomarker of VCI in at-risk subjects without atrial fibrillation.